(untitled) (Delta Medical College Journal, 2013)
Background: Diabetic retinopathy is the commonest complication that occurs from the very beginning in patients with diabetes mellitus (DM). DM itself leads to increased homocysteine (Hcy) level. It is postulated that hyperhomocysteinaemia causes retinal vascular damage as Hcy is an established vasculotoxic agent and auto-oxidation of Hcy leads to oxidative stress, endothelial dysfunction, platelet activation and thrombus formation. Objective: The aim of the study was to evaluate the serum Hcy in newly diagnosed type 2 diabetic subjects with diabetic retinopathy. Materials and method: A case control study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka, during the period of January 2006 to December 2007. Total 85 newly diagnosed type 2 diabetic subjects were included in this study, 40 were case having retinopathy and 45 were age and sex matched control without retinopathy. Serum Hcy was measured and compared between case and control. Results: Serum Hcy level in cases was significantly higher (p<0.05) compared to that of control (15.11±5.49 ?mol/L vs. 12.59±4.01 ?mol/L). Odds ratio was also determined for hyperhomocysteinemia (OR=2.23; CI 0.9-5.45). Conclusion: Hyperhomocysteinaemia is associated with diabetic retinopathy in newly diagnosed type 2 diabetes. DOI: http://dx.doi.org/10.3329/dmcj.v1i2.15916 Delta Med Col J. Jul 2013;1(2):37-41